Investigation of thrust vector angle control law based on micro-turbojet engine - Shaoqing Chi; Yunsong Gu; Dongsheng Gong; Linkai Li (AIP Advances, 2022)
The fluid thrust vectoring nozzle has a fixed profile, few moving parts, and lightweight structure, providing effective flight control for high maneuvering aircraft. The nonlinear control law of the jet deflection angle is one of the critical problems of fluid thrust vector technology. However, the research on the deflection control law of the thermal jet in a fluid thrust vectoring nozzle is not ideal. In this paper, the control law of micro-turbojet engines under a thermal jet is studied by numerical simulations and experiments. The numerical results show that the nonlinear control law of the jet deflection angle is caused by the vortex structure between the main jet and the nozzle wall. The numerical results show that the passive flow control method can effectively change the vortex structure distribution on the nozzle wall by changing the shape of the nozzle outlet structure. This change of flow structure can effectively make the jet deflection control law close to linear. The experimental results show that the nozzle with this configuration can continuously and controllably deflect the main jet under the thermal jet of the micro-turbojet engine. The vector deflection control law of this nozzle configuration is close to linear and has less thrust loss.